2011
DOI: 10.1007/s00436-011-2714-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expressions of MHC-DQB1 mRNA in Chinese merino sheep infected with Echinococosus granuclosus

Abstract: The purpose of the present study was to investigate the dynamic changes of MHC-DQB1 mRNA expression in sheep infected with Echinococosus granuclosus. A total of 14 healthy Chinese merino sheep were experimentally infected with E. granuclosus. The blood samples were collected on days 0 (initiation of the infection), 7, 21, 30, and 60 post-infection, respectively. On day 60 post-infection, when the experiment was terminated, all sheep were euthanized to make a diagnosis of cystic echinococcosis (CE) using routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Chinese Merino sheep, well known for their characteristics of good wool and meat production, is beneficial to local sheep industry; however, they are relatively more susceptible to CE (Hui et al, 2012). The prevalence of CE in Chinese Merino sheep causes considerable economic problems due to the loss of production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese Merino sheep, well known for their characteristics of good wool and meat production, is beneficial to local sheep industry; however, they are relatively more susceptible to CE (Hui et al, 2012). The prevalence of CE in Chinese Merino sheep causes considerable economic problems due to the loss of production.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that different MHC-DQB1 mRNA expression levels were detected between different outcomes of CE infections in Chinese Merino sheep (Hui et al, 2012). So, in this study, we were curious to see whether variation in MHC-DQB1 was associated with susceptibility or resistance to CE in Chinese Merino sheep.…”
Section: Introductionmentioning
confidence: 99%